Characteristics of Compost from Balinese Cattle Dung (CD) and Rice Straw (RS) using White Rot Fungus (Wrf) (Ganoderma sp) As Bioactivators (Jurnal Ilmu dan Teknologi Hasil Ternak, 2020)
To maximize the performance of the fermentation process, there is a need for a biactivator. The purpose of this study was to evaluate the characteristics of compost-based waste from cattle dung (CD) combined with rice straw (RS) by applying white rot fungus (Wrf) (Ganoderma sp) as a bioactivator.  In this study, 6 types of treatments have been applied, namely T1(CD:RS)(25%:75%)+5% of Wrf; T2(CD:RS)(50%:50%)+5% of Wrf; T3(CD:RS)(75%:25%)+5% of Wrf; T4 (CD:RS)(25%:25%)+0% of Wrf; T5(CD:RS)(50%:50%)+0% of Wrf; T6 (CD:RS)(75%:25%)+0% of Wrf. The study was designed experimentally using a completely randomized design (CRD), 6 treatments with 3 replications.  Based on the research results, the difference in the ratio of CD to RS and the use of Wrf bioactivator has a significant effect (p<0.05) in increasing the pH, temperature, C-organic and C/N ratio in compost. However, this difference had no significant effect (p>0.05) on the C-organic value. The pH value of compost was obtained with variations of 5.50±0.43-6.73±0.06. Temperature of compost is in the range of values 24.00±0.00-25.67 ±0.58 ºC. The C-organic value is in the range of 24.38±0.48-31.32±0.80%, while the N-organic value varies at 1.34±0.11-2.10±0.15%. The C/N ratio is in the range of 15.00± 0.11-19.33±1.15. Based on the interaction, the results showed that there was a significant interaction (p>0.05) between the use of Wrf bioactivator with the ratio of CD to RS on the parameters of pH, N-organic and C/ Nratio, while, C-organic and temperature had no significant effect.  The results of the study was concluded that several test parameters produced compost characteristics that were in accordance with Standar Nasional Indonesia (SNI) and the Regulation of the Minister of Agriculture of the Republic of Indonesia. Compost production using T3 treatment ((CD:RS)(75%:25%) + 5% of Wrf) produces the best characteristics compared to other treatments.